Simple index of functional connectivity at rest in Multiple Sclerosis fatigue. Issue 5 (May 2017) - Buyukturkoglu, Korhan; Porcaro, Camillo; Cottone, Carlo; Cancelli, Andrea; Inglese, Matilde; Tecchio, Franca
Highlights: EEG-based functional connectivity at rest (FCR) was tested in Multiple Sclerosis (MS) patients with fatigue. Beta temporo-parietal FCR was higher in fatigued MS patients than controls. MS fatigue severity correlated directly with beta temporo-parietal FCR. Abstract: Objective: To investigate the EEG-derived functional connectivity at rest (FCR) patterns of fatigued Multiple Sclerosis (MS) patients in order to find good parameters for a future EEG-Neurofeedback intervention to reduce their fatigue symptoms. Methods: We evaluated FCR between hemispheric homologous areas, via spectral coherence between pairs of corresponding left and right bipolar derivations, in the Theta, Alpha and Beta bands. We estimated FCR in 18 MS patients with different levels of fatigue and minimal clinical severity and in 11 age and gender matched healthy controls. We used correlation analysis to assess the relationship between the fatigue scores and the FCR values differing between fatigued MS patients and controls. Results: Among FCR values differing between fatigued MS patients and controls, fatigue symptoms increased with higher Beta temporo-parietal FCR ( p = 0.00004). Also, positive correlations were found between the fatigue levels and the fronto-frontal FCR in Beta and Theta bands ( p = 0.0002 and p = 0.001 respectively). Conclusion: We propose that a future EEG-Neurofeedback system against MS fatigue would train patients to decrease voluntarily the beta coherence between the homologous temporo-parietal areas. Significance: We extracted a feature for building an EEG-Neurofeedback system against fatigue in MS.